The Influence of Service Quality and Trust in JNE Express Shipping Services for Loyalty Deli Serdang Consumers - Jopinus Saragih (PT Inovasi Pratama Internasional, 2023)
This study aims to analyze the effect of service quality on delivery services on customer satisfaction of JNE Express Deli Serdang. This study uses three variables, namely Service Quality, Trust and Consumer Loyalty. The population in this study are consumers or users of JNE Express Deli Serdang. Samples were taken as many as 68 respondents using a non-probability sampling technique, namely a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample, where this research uses purposive sampling, namely a sampling technique using consideration that it is assumed that in this way information can be obtained that is correct and reflects the population . The data analysis method used is in the form of validity and reliability tests, classical assumption tests, multiple linear regression analysis, T-test and F-test and the coefficient of determination (R2). Based on data analysis, the results show that the indicators in this study are valid and reliable. In the classical assumption test the data is normally distributed, there is no heteroscedasticity and multicollinearity. in the service quality variable hypothesis test, trust has a significant effect on consumer loyalty. And the most influential variable is the trust variable with a regression coefficient of 0.265.